Endothelin, Astrocytes and Glaucoma - Prasanna, Ganesh (2010)
It has become increasingly clear that astrocytes may play an important role in the genesis of glaucoma. Astrogliosis occurs in response to ocular stress or the presence of noxious stimuli. Agents that appear to stimulate reactive gliosis are becoming increasingly clear. One class of agents that is emerging is the endothelins (ETs; specifically, ET-1). In this review we examine the interactions of ET-1 with astrocytes and provide examples where ET-1 appears to contribute to activation of astrocytes and play a role in the neurodegenerative effects that accompany such reactivation resulting in astrogliosis. These actions are presented in the context of glaucoma although information is also presented with respect to ET-1's role in the central nervous system and brain. While much has been learned with respect to ET-1/astrocyte interactions, there are still a number of questions concerning the potential therapeutic implications of these findings. Hopefully this review will stimulate others to examine this potential.